Implementasi Payment Gateway Pada Aplikasi Toko Mebel Menggunakan MERN Stack - Hakim, Adya Abdu Azizul; Setiaji, Galet Guntoro; Rifa'i, Ahmad (STMIK Sinar Nusantara, 2025)
The advancement of technology in the e-commerce sector has driven traditional stores to transition to digital systems in order to enhance transaction efficiency and product management. Mebel Amanah is a furniture store owned by Mr. Hj. Wahyono, located in Plebean, Batang. Previously, Mebel Amanah only accepted in-person payments, which proved to be less effective, particularly for customers who were unable to visit the store directly. Although bank transfer options were available, the store provided only one bank account number, posing challenges for customers using different banks due to additional administrative fees. To address this issue, an online payment system using Midtrans was implemented, offering various payment methods such as ATM/bank transfer, credit/debit cards, e-wallets, and virtual accounts. The Furniture Store Application also includes a product management feature that displays product names, prices, descriptions, and stock information in real-time. This application was developed using the MERN Stack and follows the Waterfall development model, which includes system requirement analysis, system design, implementation, testing, deployment and maintenance phases. The implementation results demonstrate that integrating the Midtrans payment gateway improves payment flexibility and speeds up transaction processes. Furthermore, the product management feature allows customers to easily check product availability without needing to inquire directly. In conclusion, the furniture store application not only facilitates transaction processes but also supports the digital transformation of furniture business operations.